Analysis of Instruments for Assessment of Basic Movement Skills PJOK Elementary School - Rahma Dewi; Indah Verawati; Bessy Sitorus Pane; Nurkadri Nurkadri (UNIB Press, 2022)
This study aims to analyze the validity results and the reliability and practicality of the basic movement skills assessment instrument for primary school PJOK. The research method in this study uses an R & D development model using an analysis modified by researchers into three stages, namely define, design and develop. The results of the validity were analyzed using the T Score from several aspects assessed by experts with an ideal percentage value of 90% with a very good category and suitable for use. The results of instrument reliability on a small scale use GENOVA analysis, for locomotor indicators (0.90), manipulative indicators (0.91). The practicality of the instrument which was analyzed using a T score obtained an average score of 52.33 and from the T score of each rater I (49), rater II (54), and from rater III obtained a T score (54) and based on the teacher's assessment of the instrument assessment of basic movement skills is quite practical. In conclusion, the instrument for assessing basic movement skills in PJOK learning that was developed has met the requirements of validity, reliability and practicality, as an evaluation tool that can be used further by primary school PJOK teachers.